Fusion pore formation and expansion induced by Ca(2+) and synaptotagmin 1 - Lai, Ying (National Academy of Sciences, 2013)
Fusion pore formation and expansion, crucial steps for neurotransmitter release and vesicle recycling in soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-dependent vesicle fusion, have not been well studied in vitro due to the lack of a reliable content-mixing fusion assay. Using methods detecting the intervesicular mixing of small and large cargoes at a single-vesicle level, we found that the neuronal SNARE complexes have the capacity to drive membrane hemifusion. However, efficient fusion pore formation and expansion require synaptotagmin 1 and Ca(2+). Real-time measurements show that pore expansion detected by content mixing of large DNA cargoes occurs much slower than initial pore formation that transmits small cargoes. Slow pore expansion perhaps provides a time window for vesicles to escape the full collapse fusion pathway via alternative mechanisms such as kiss-and-run. The results also show that complexin 1 stimulates pore expansion significantly, which could put bias between two pathways of vesicle recycling.